2019
DOI: 10.1161/circresaha.118.314642
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbial Associations to Plasma Metabolites Linked to Cardiovascular Phenotypes and Risk

Abstract: Rationale: Altered gut microbial composition has been linked to cardiovascular diseases (CVDs), but its functional links to host metabolism and immunity in relation to CVD development remain unclear. Objectives: To systematically assess functional links between the microbiome and the plasma metabolome, cardiometabolic phenotypes, and CVD risk and to identify diet-microbe-metabolism-immune interactions in well-doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
112
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(123 citation statements)
references
References 68 publications
(72 reference statements)
0
112
0
Order By: Relevance
“…In recent decades, the term ‘cardiometabolic syndrome’ has been mentioned in the context of various conditions (Yang et al , ,). A study of a population cohort identified metabolic risks related to microbiome functional parameters, such as lipoprotein particle composition, fatty acid saturation, and carbohydrate and sugar derivative metabolism that could predict the probability of CVD consequences (Kurilshikov, et al , ). A growing body of studies suggests that the gut microbiota can mechanistically impact host lipid levels.…”
Section: The Link Between the Gut Microbiota And Cvd‐related Risk Facmentioning
confidence: 99%
“…In recent decades, the term ‘cardiometabolic syndrome’ has been mentioned in the context of various conditions (Yang et al , ,). A study of a population cohort identified metabolic risks related to microbiome functional parameters, such as lipoprotein particle composition, fatty acid saturation, and carbohydrate and sugar derivative metabolism that could predict the probability of CVD consequences (Kurilshikov, et al , ). A growing body of studies suggests that the gut microbiota can mechanistically impact host lipid levels.…”
Section: The Link Between the Gut Microbiota And Cvd‐related Risk Facmentioning
confidence: 99%
“…Microorganisms colonizing the cervicovaginal microenvironment produce a broad range of metabolites that are important for genital health. However, the relationship between taxonomic and functional shifts of the host's microbiome and peripheral site metabolomes remains largely unexplored, and only a few studies so far have characterized the associations of individual taxa with circulation metabolome using plasma [27] and serum [25,26]. Nevertheless, a recent study aimed to identify taxonomic and metabolic alterations in the cervicovaginal microbiome and urine metabolome in women at risk of preterm premature rupture of the membranes found functional associations between microbiome and metabolome, which could facilitate an appropriate response to a given treatment regime [31].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies associating the microbiome and systemic health were conducted via assessment of interactions between the gut microbiome and gut metabolome [23]. A popular strategy now is to explore associations between the gut microbiome and serum metabolome due to the ability of circulating metabolites to translocate through the host's barriers, and therefore, giving the potential for the identification of systemic health effects [24][25][26][27]. Since metabolites from the gut are absorbed into the circulation and finally excreted through urine [28], recent studies suggest that exploration of the association between urine metabolome and host-microbiome may complement sequencing-based approaches with a functional readout of the gut microbiome [29].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the combination of metagenomics and metabolomics will provide a more comprehensive and insightful understanding of the complex microbiome–host interactions and can unravel potential mechanism linking microbiome with host health and disease. Despite a decade ago the marriage between metagenomics and metabolomics was proposed , only few human studies have combined metagenomics and urine , plasma or faecal metabolomics () to dissect metabolic disease. In addition, although all these biofluids contain host and gut microbiota cometabolites, microbial‐derived metabolites may account for up to 90% of the faecal metabolome , whereas they only represent about 10% and 3% of the plasma and urinary metabolome , respectively.…”
Section: Metagenomics and Metabolomics: An Utterly Compelling Marriagementioning
confidence: 99%